3248 Fluorescence-Guided Neurosurgery with 5-Aminolevulinic-Acid and Second-Window-Indocyanine-Green: A murine model and investigation into suitable cell lines. (27th March 2019) - Cho, Steve; Lee, John Y.K.; Sheikh, Saad
Abstract : OBJECTIVES/SPECIFIC AIMS: This study aims to understand the utility of 5-ALA and SWIG in detecting areas of neoplasm in a murine model of GBM. Primary outcome is the distribution of the two dyes in comparison to the true tumor extent; the sensitivity, specificity, PPV, and NPV of both dyes will be calculated. The secondary outcome is the suitability of existing cell-lines used for GBM research for studies in fluorescence-guided surgery. METHODS/STUDY POPULATION: Two cell lines are used for this research: U87, derived from human GBM; and GL261, derived from rodent stem cells. U87 are implanted intracranially into 6-week old athymic, nude, female mice, while GL261 are implanted intracranially into 10-week old female C57BL/6 mice. The mice are weighed every 3 days to monitor health and bioluminescence imaging is performed between 7-10 days after implantation to confirm tumor implantation and monitor tumor growth. The mice are sacrificed between 10-21 days after implantation. 5mg/kg of intravenous ICG is administered 24-hours prior to harvest and 250mg/kg of intraperitoneal 5-ALA is administered 3-hours prior to harvest. Once the mice are sacrificed, their brains are quickly harvested and placed in cold formalin. Using a high-resolution Odyssey CLx scanner, near-infrared fluorescence from ICG is captured in coronal cross sections of the brains through the tumor. Similarly, 5-ALA fluorescence is imaged using a 405nm LED excitation source and 610-690nm bandpass filter. Afterwards, slices of the brain are stained with H&E, which serves as the gold-standard of the extent of tumor. Images from ICG, 5-ALA, and H&E can then be compared using ImageJ to compare the extent of tumor to the distribution of the dyes. RESULTS/ANTICIPATED RESULTS: In separate, previous studies in humans, both 5-ALA and SWIG have demonstrated utility in detecting residual neoplasm in HGG resections. In general, 5-ALA is more specific for areas of neoplasm, while SWIG is more sensitive. Thus, I anticipate that in this study, SWIG will show a greater distribution than 5-ALA, with SWIG distributing to areas beyond the tumor and 5-ALA distributing within, but not completely covering, the tumor. SWIG's sensitivity and NPV for detecting tumor should be >90%, while its specificity and PPV may be closer to 50%. For 5-ALA, specificity and PPV should be close to 80-90%, but its sensitivity and NPV may be <50%. In terms of cell-line, preliminary results suggest that U87 cells are not suitable for research involving 5-ALA. We suspect that this is partly due to the limited infiltrative nature of U87 cells; in fact, the cells form a spherical mass, imitating metastases rather than true HGGs. The U87 masses do not have significant vascularity, which likely limits the amount of 5-ALA that can distribute to inside the tumor. DISCUSSION/SIGNIFICANCE OF IMPACT: 5-ALA is currently the only FDA-approved agent for fluorescence-guided neurosurgery. However, it has multiple limitations, which ultimately results in its low sensitivity and NPV. Our novel technique, which has demonstrated much higher sensitivity at the cost of specificity, offers an alternative that may help surgeons better achieve total resections in the operating room. These two agents have not been compared directly in humans or mice. Thus, this experiment sets up an important precedent, on which a human clinical trial comparing the two agents' effects on resection rates and patient outcome can be performed. Ultimately, this work will lay the foundation for future research into fluorescence-guided neurosurgery, both in the visible and NIR spectrum.